(untitled) (Journal of the College of Basic Education, 2022)
Our study examines one of the important transformations in the art of ceramics before and after the warThe second world is represented by the production of potters (Ruth Duckworth) and the impact it had on ceramicsOver the nearly seventy years of creativity and continuous production, this vast achievement is openOn many studies, one of which is the subject of our current research in monitoring and revealing how it worksAnalytical mechanisms and structures in her art The study, in its first chapter, dealt with this problem 9Temporal, spatial and objective boundaries and the procedural definition of the terms in the researchThe second chapter also establishes the intellectual and cognitive construction of the concept of analysis, composition, and work constructsThe technical and the most important objective indicators that resulted from dealing with these concepts in the sourcesLiterature and the third chapter included the research community